Making space for women: civil society organizations, gender and hydropower development in the Mekong region - Phimphakan Lebel (2018)
© 2018 Informa UK Limited, trading as Taylor & Francis Group Large-scale hydropower development disrupts local livelihoods and resource access. Adverse impacts are often greater for women than men, but also large for children, the elderly, poorer households and ethnic minorities. Burdens of resettlement often fall disproportionately on already disadvantaged individuals. The purpose of this study was to evaluate how international, national and local civil society organizations (CSOs) have addressed gender in hydropower development in the Mekong Region. Four CSO orientations are distinguished: communitarian, environmentalist, knowledge-based and feminist. Common activities of CSOs were to share information, to expand participation and to mobilize development. The extent to which these activities were promoted and appear to be making space for women depended on the types of CSOs and women and men targeted or otherwise involved.